Susceptibility of various Gram-negative bacteria to antibacterial agents: SMART in China 2019–2020 - Ying Fu; Yueliang Chen; Yanfei Wang; Bingyan Yao; Pengcheng Li; Yunsong Yu (BMC Microbiology)
Abstract Background The Study for Monitoring Antimicrobial Resistance Trends (SMART) is an international surveillance program longitudinally monitoring aerobic and facultative Gram-negative bacteria (GNB) involvement in infections and their antimicrobial resistance profiles. Here the incidence and resistance patterns of Chinese GNB isolates from bloodstream infections (BSI), intraabdominal infections (IAI), respiratory tract infections (RTI) and urinary tract infections (UTI) to commonly used antibacterial agents has been updated. 4,975 GNB isolates collected from 22 hospitals across 7 regions of China from 2019 to 2020 were analyzed. Antimicrobial minimum inhibitory concentrations were assessed using broth microdilution, and susceptibility interpretations followed the breakpoints of European Committee on Antimicrobial Susceptibility Testing 2022 or Clinical and Laboratory Standards Institute. Results This study affirmed that Escherichia coli (Ec) was the most commonly identified GNB (32.1%) and then Klebsiella pneumoniae (Kp) (25.3%), Pseudomonas aeruginosa (Pa) (13.9%) and Acinetobacter baumannii (10.5%). The detection rates of carbapenem-resistant (CR) Enterobacterales varied across major infection sites, ranging from 10.3% in UTI to 18.9% in RTI. Specifically, the detection rates of CR-Kp and CR-Pa ranged from 16.2% in IAI to 35.8% in UTI and from 16.1% in UTI to 38.0% in RTI, respectively. Extended-spectrum β-lactamases (ESBL)-producing Ec and Kp bacteria exhibited over 91.7% susceptibility to carbapenems and at least 87.8% susceptibility to amikacin and colistin, but showed lower susceptibility to piperacillin/tazobactam (57.5–86.2%), levofloxacin (10.8–39.7%) and aztreonam (15.3–27.6%) across different infection sources. Amikacin showed higher efficacy against CR strains compared to other commonly used antibacterial drugs, with 80.0% susceptibility against CR-Ec and 82.3% susceptibility against CR-Pa, while only 36.3% susceptibility was observed against CR-Kp. Conclusions The study found varying incidences of CR isolates in Chinese hospitals. Treatment options remained limited due to resistance to multiple antibacterial agents. Carbapenems demonstrated effective antimicrobial in vitro activity against ESBL-producing Enterobacterales found in BSI, IAI, UTI and RTI, outperforming broad-spectrum cephalosporins and other β-lactamase inhibitors.